Heteroatom-doped nanoporous carbon derived from MOF-5 for CO2 capture - Ma, X.; Li, L.; Chen, R.; Wang, C.; Li, H.; Wang, Shaobin (Elsevier BV North-Holland, 2018)
Four nanoporous carbons (MUCT) were prepared from metal-organic framework (MOF-5) template and additional carbon source (i.e. urea) by carbonization at different temperatures (600–900 °C). The results showed that specific surface area of four samples was obtained in the range from 1030 to 2307 m 2 g -1 . By changing the carbonization temperature it can finely tune the pore volume of the MUCT, which having a uniform pore size of around 4.0 nm. With an increasing carbonization temperature, the micropore surface area of MUCT samples varied slightly, but mesopore surface area increased obviously, which had little influence on carbon dioxide (CO 2 ) adsorption capacity. The as-obtained sample MUC900 exhibited the superior CO 2 capture capacity of 3.7 mmol g -1 at 0 °C (1 atm). First principle calculations were conducted on carbon models with various functional groups to distinguish heterogeneity and understand carbon surface chemistry for CO 2 adsorption. The interaction between CO 2 and N-containing functional groups is mainly weak Lewis acid-base interaction. On the other hand, the pyrrole and amine groups show exceptional hydrogen-bonding interaction. The hydroxyls promote the interaction between carbon dioxide and functional groups through hydrogen-bonding interactions and electrostatic potentials, thereby increasing CO 2 capture of MUCT.